(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
This article presents the restructuring and reliability analysis of a measurement instrument implemented for the postgraduate teaching evaluation of a Public University in the Southeast of Mexico. The need arises from the fact that the dimensions and variables that made it up were not objective to carry out the pertinent analyzes in the teaching-learning evaluation processes implemented by the teacher inside the classroom, whether the latter was face-to-face or virtual; It is for this reason that, in the restructuring of said instrument, 6 dimensions made up of 31 items are proposed; therefore, through the reliability analysis called Cronbach’s Alpha, a result of .912 was obtained, which is considered acceptable for its implementation and development.